Effect of lacosamide on cortical spreading depolarization in mice - Chisato Iba; Miyuki Unekawa; Keiko Ihara; Yoshikane Izawa; Jin Nakahara; Tsubasa Takizawa (The Journal of Headache and Pain)
Abstract Background Antiseizure medications are often used as preventive treatment of migraine in appropriate cases; however, the efficacy of lacosamide (LCM), a sodium channel blocker, in preventing migraine attacks remains unclear. Cortical spreading depolarization (CSD) refers to a wave of slowly propagating depolarization across the cerebral cortex. CSD animal models have been extensively used to investigate migraine attacks and evaluate the effects of migraine medication. Herein, we examined the effects of single dose LCM (40 mg/kg) on CSD sensitivity in a mouse model. Findings Thirty-two C57BL/6 mice (male, n = 16; female, n = 16) were intraperitoneally injected with either LCM (40 mg/kg) or saline before CSD sensitivity testing. Potassium chloride (KCl) was administered to induce CSD, and the CSD threshold, frequency, and propagation velocity were determined. The average CSD frequency induced by 1 M KCl was significantly lower (p = 0.030) and the CSD propagation velocity tended to be lower in the female LCM group than in the saline group. However, no significant differences were observed in any of the three CSD parameters in male mice. Conclusions In female mice, single dose LCM treatment significantly reduced CSD frequency induced by KCl. Further investigations are warranted to assess the clinical potential of LCM in preventing migraine.